2022
DOI: 10.3390/biomedicines10102475
|View full text |Cite
|
Sign up to set email alerts
|

Altered Extracellular Matrix as an Alternative Risk Factor for Epileptogenicity in Brain Tumors

Abstract: Seizures are one of the most common symptoms of brain tumors. The incidence of seizures differs among brain tumor type, grade, location and size, but paediatric-type diffuse low-grade gliomas/glioneuronal tumors are often highly epileptogenic. The extracellular matrix (ECM) is known to play a role in epileptogenesis and tumorigenesis because it is involved in the (re)modelling of neuronal connections and cell-cell signaling. In this review, we discuss the epileptogenicity of brain tumors with a focus on tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 252 publications
0
3
0
Order By: Relevance
“…The first specialized form is perineuronal nets (PNNs), which mostly envelop the inhibitory parvalbumin (PV) expressing interneurons. While the composition of PNNs may vary across different brain regions and change with age, their backbone is composed of chondroitin sulfate proteoglycans (CSPG) lecticans, such as aggrecan, brevican, and neurocan, whose amino terminal regions bind to hyaluronan while their carboxy terminal regions bind to tenascin [ 4 , 5 ]. The second CNS-specific form of the ECM is the basement membrane (BM), including the meningeal BM, which surrounds the pial surfaces, and the vascular BM, which surrounds blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The first specialized form is perineuronal nets (PNNs), which mostly envelop the inhibitory parvalbumin (PV) expressing interneurons. While the composition of PNNs may vary across different brain regions and change with age, their backbone is composed of chondroitin sulfate proteoglycans (CSPG) lecticans, such as aggrecan, brevican, and neurocan, whose amino terminal regions bind to hyaluronan while their carboxy terminal regions bind to tenascin [ 4 , 5 ]. The second CNS-specific form of the ECM is the basement membrane (BM), including the meningeal BM, which surrounds the pial surfaces, and the vascular BM, which surrounds blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…It has been experimentally shown that the extracellular matrix of the brain "may contain memory traces of local neural network activity" [28] and participates in the modulation of various types of memory [34], as well as potentially contributing to the formation of epileptogenesis [35][36][37]. Burst activity is known to underlie both information processing [38] and storage [39][40][41], including in memory traces [42], as well as in neuropathologies such as epilepsy [43].…”
Section: Introductionmentioning
confidence: 99%
“…There is a prominent activation of both the innate and adaptive immune systems in glioneuronal tumors [30,31]. Altered extracellular matrix (ECM) is another risk factor for epileptogenicity [32 ▪ ]. In this regard, GGs have a higher expression of ECM-related genes, and the expression of laminins, collagens, thrombospondins, and various integrins is higher in GGs than in control tissue [33].…”
Section: Introductionmentioning
confidence: 99%